Capital intelectual y productividad de los pequeños floricultores del barrio Patután del cantón Latacunga - Analuisa Maiguashca, Katherine Maribel (2022)
The present investigation was carried out with the flower growers of the Patután neighborhood, the identified problem was oriented in the limited knowledge of the human, commercial, technological, financial capital that prevents the flower growers from being productive, this lies in two main causes: the non-existence of a system organized training that causes their productivity to be low, the inadequate management of an accounting system that generates a deficient administration of economic resources. The present investigation had a quantitative, descriptive and correlational approach through the application of a survey addressed to 80 flower growers from the Patután neighborhood, the information gathering was carried out in person, from the results of the survey the analysis was obtained. situation of intellectual capital and productivity.